Pengaruh Pemberian Larutan Kulit Kayu Faloak (Sterculiaquadrifida) Dalam Air Minum Terhadap Performa Ayam Broiler - Kaho, Ama Try Putra; Dillak, Sutan Y.F.G; Sinlae, Markus (Yayasan Sumber Daya Manusia Cerdas, 2024)
This study aims to evaluate the effect of giving faloak bark solution in drinking water on feed intake, water intake, daily weight gain and feed conversion ratio . This study used a complete randomized design consisting of 4 treatments and 5 replications, of wich had 5 chickens. The treatments given were R0 = without the addition of faloak bark solution in drinking water, R1=1 ml of faloak bark solution/l drinking water, R2= 1.5 ml of faloak bark solution/l drinking water, R3=2 ml of faloak bark solution/l drinking water. The variables measured of the study included feed intake, water intake, daily weight gain and feed conversion ratio. The results of statistical analysis showed that the administration of faloak solution in drinking water had not effect (P>0.05) on feed intake, water intake, daily weight gain and feed conversion ratio. Based on the results of the study, it can be concluded that the administration of faloak bark solution up to 2 ml / l of drinking water has not effected feed intake, water intake, daily weight gain and feed conversion ratio.